Rapid genome sequencing for critically ill infants: an inaugural pilot study from Turkey - Guner Yilmaz, Bengisu; Akgun-Dogan, Ozlem; Ozdemir, Ozkan; Yuksel, Bayram; Hatirnaz Ng, Ozden; Bilguvar, Kaya; Ay, Beril; Ozkose, Gulsah Sebnem; Aydin, Eylul; Yigit, Ayca; Bulut, Aybike; Esen, Fatma Nisa; et al. (Frontiers in Pediatrics, 2024)
Introduction: Rare and ultra-rare genetic conditions significantly contribute to infant morbidity and mortality, often presenting with atypical features and genetic heterogeneity that complicate management. Rapid genome sequencing (RGS) offers a timely and cost-effective approach for diagnosis, aiding in early clinical management and reducing unnecessary interventions. This pilot study represents the inaugural use of NGS as a diagnostic instrument for critically ill neonatal and pediatric ICU patients in a Turkish hospital setting. Methods: Ten infants were enrolled based on predefined inclusion criteria, and trio RGS was performed. The mean age of participants was 124 days, with congenital abnormalities being the most common indication for testing. Three patients had consanguineous parents. The mean turnaround time from enrollment to delivery of results was 169 hours, with a diagnostic yield of 50%. Results: Three patients received a definitive molecular diagnosis, impacting their clinical management. Two patients benefited from the exclusion of Mendelian conditions, leading to alternative diagnoses. Discussion: This study demonstrates the feasibility and results of RGS in Turkish hospital settings, emphasizing the importance of timely genetic diagnosis in reducing the diagnostic odyssey for families and improving patient care. Further research is needed to evaluate the cost-effectiveness and applicability of RGS in the Turkish healthcare system for children with diseases of uncertain etiology.